Playful-consumption experiences and subjective well-being: Children's smartphone usage - Abbasi, A.Z. (Elsevier B.V., 2021)
The study aims to investigate the factors that contribute to children's subjective well-being. We used playful-consumption experiences in children's smartphone usage to determine their subjective well-being. In total, 210 valid responses were obtained from the parents and analyzed using PLS-SEM in SmartPLS 3.2.8. The results of the measurement model revealed that the investigated constructs were reliable and valid. The findings based on the structural model revealed that children's emotional involvement, enjoyment, and sensory experiences with smartphones positively influenced their subjective well-being. However, children's fantasy, escapism, arousal, and role-projection experiences with smartphones failed to impact children's subjective well-being. The study is among the pioneers to investigate children's subjective well-being from the perspective of smartphone usage and playful-consumption experiences. Â© 2020 Elsevier B.V.